Internationalizing colonial war: On the unintended consequences of the interventions of the International Committee of the Red Cross in South-East Asia, 1945–1949 - van Dijk, B (Oxford University Press, 2020)
What is the relationship between decolonization and international law? Most historians agree that empires framed their colonial wars as emergencies in order to escape international scrutiny. After 1945, however, those same imperial powers invited the International Committee of the Red Cross (ICRC) to intervene in their wars of decolonization while resisting an official state of war. This article seeks to solve this puzzle by drawing attention to the ICRC’s critical part in reshaping the international legal system regarding colonial war in the critical years before the Algerian War of Independence (1954–62) and the Bandung Conference (1955). In this formative period, the organization, together with anti-colonial activists, played a transformative role in contesting accepted ideas of global governance and international law while providing a new stage for anti-colonial resistance, with far-reaching consequences, not just for the ICRC’s own institutional future, but also for the legitimization of (post-)colonial sovereignty in the twentieth century.